Areas of endemism: travelling through space and the unexplored dimension. Issue 2 (3rd March 2016) - Noguera-urbano, Elkin A.
Abstract : The current concept of areas of endemism assumes that they are geographic areas where there is spatial congruence of at least two endemic taxa. When this congruence is non-random, areas of endemism are explained by historical and ecological factors. Space has been the main dimension of analysis of areas of endemism, and the role of the time dimension in areas of endemism remains unclear. Phylogenetic information is a source of temporal information to explore the structure of the areas of endemism. I review the concept of areas of endemism and discuss their conceptual models (structure and boundaries). I propose four scenarios about the structural integration of endemic taxa in the space-time dimensions into areas of endemism. A better understanding of how to interpret areas of endemism can be analysed using phylogenetic information from endemic taxa to test simultaneous divergence and to propose temporal strata. Although the evolutionary relationships of the space and time dimensions have rarely been characterized in areas of endemism, I used this conceptual framework to interpret the Andean area of endemism and its evolution.